Open Adoption Placement by Birth Mothers in Their Twenties. Issue 6 (November 2017) - Clutter, Lynn B.
Abstract: Purpose: The purpose of this study was to summarize birth mothers' descriptions of unplanned pregnancy experienced in their twenties and how open adoption influenced their lives. Study Design and Methods: Naturalistic inquiry was used with purposive sampling from one agency and telephone interviews of women who experienced unplanned pregnancy in their twenties and relinquishment through open adoption. Recorded, transcribed, and deidentified interviews were analyzed for qualitative themes. Results: Fifteen participants judiciously weighed the open adoption decision. Over half parented other children prior to placement. Most knew they could not have parented this child due to life stressors. Placement was a hard decision, but ongoing contact with birth child and adoptive family was valued. Open adoption processes made them stronger by being happy that their child experienced family life with greater opportunities than birth mothers could offer at the time. Summarized themes used the acronym COMMITTED: C—care deeply about what is best for the child, O—ongoing open adoption: good and hard, M—meeting together regularly, M—moving on in personal growth, accomplishments, and milestones, I—independence from previous stressors or crises, T—transitions, T—therapeutic support, E—emotions, D—depression giving way to deepened strength and personal direction. Clinical Implications: Open adoption is reinforced as a positive resolution of unintended pregnancy for birth mothers in their twenties. Abstract : Open adoption can have benefits for all members of the adoption triad, the birth mother, the adoptive family, and the adoptee. This study offers further evidence of these benefits by exploring the experiences of 15 birth mothers who participated in open adoption in their twenties.